TECHNOLOGICAL LITERACY AND RESOURCE MANAGEMENT IN SME INCOME - Nanda Oktasavira Nanda Oktasavira; Hadi Ismanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2022)
The characteristics of SMEs continue to be highlighted, but the exciting thing behind their strengths are acute unresolved problems such as technology skills, human resource management and finance. Borrowing assumptions from resource-based theory, this study tries to examine the effect of technological literacy, working capital, and labour management on the income of SMEs. The sample consisted of 100 SMEs in 14 industries randomly assigned proportionally based on their industry type and filled out the research questionnaire directly. The collected questionnaires were tabulated and analyzed using the Partial Least Square method. The results show that technological literacy, working capital, and labour management positively affect business income individually and simultaneously. These findings record that 45 per cent of the sample do not integrate their products with competitors because they are less skilled in using information media to measure competitors' capabilities. In practice, technological literacy can be transformed for production, administration, and product marketing activities to maximize business income.